3D computational fluid-structure interaction model for the estimation of propulsive forces of a deformable monofin - Bideau, N.; Razafimahery, F.; Monier, L.; Mahiou, B.; Nicolas, G.; Bideau, B.; Rakotomanana, L. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: The current paper contributes to the investigations of biomechanical aspects of propulsion of swim fins. Indeed, we describe a new method that is devoted to computation of propulsive forces generated by flexible monofin. From this method, we calculate the added mass and show the great impact of this parameter. METHODS: A 3D fluid-structure model with inertial coupling is developed. The monofin is assumed to be a deformable elastic structure. The fluid is described with the acoustic pressure. The coupling results in an added mass charcterizings the energy transmission between the fin and the water. A numerical computation with the Finite Element Method (FEM) is conducted. The transient propulsive force end torque are investigated. RESULTS: The added mass of surrounding water affects significantly the eigenfrequencies and modal shapes. It can be observed that taking into account for 3D effects leads to decrease (27.71 to 40.21%) the vibration frequency of the fin. Moreover, the influence of the elasticity has been investigated and shows that he flexibility of the fin blade increases the thrust. A significant variation of the frequency of the non-harmonic thrust evolution is observed with regards to the applied stroke kinematics that are harmonically varying. DISCUSSION: To our knowledge it is the first fluid-structure interaction model for the whole monofinwater system solved by 3D FEM approach. It is based on a monolithic resolution of the whole system fluid and solid. REFERENCES: Bideau N, Mahiou B, Monier L, Razafimahery F, Bideau B, Nicolas G, Razafimahery F, Rakotomanana L (2009). 2D dynamical efficiency of a swimfin: a fluid-structure approach. Computer Methods in Biomechanics and Biomedical Engineering, 11: 53-54.